2018
DOI: 10.1590/2177-9465-ean-2017-0120
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality of adolescents living with HIV/AIDS: sources of information defining learning

Abstract: Objective: To know the sources of information of adolescents living with HIV/AIDS that define learning about sexuality. Methods:A qualitative study was performed in a Specialized Care Service of a city in the state of Rio Grande do Sul, Southern Brazil, with 15 adolescents living with HIV/AIDS. A semi-structured interview and thematic analysis were used. Results: Adolescents have built up their knowledge about sexuality, especially through relationships with friends and older family members, or through access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
3
Order By: Relevance
“…Although before the intervention we found that the variables were unsatisfactory, we now propose that the expected results were obtained, coinciding with other educational interventions already carried out, where up to 79% and 85% of satisfactory results were achieved . When comparing the data obtained with the empirical investigations carried out after the intervention, it can be seen that the results are in tune with the current trends in the effectiveness of the interventions, with the one proposed by this research being one of the most satisfactory and significant results [26][27][28][29][30][31]. The economic valuation and the social contribution are evident in that these results affect not only the individual welfare but social, with the decrease of these infections from an early age, the risk of infection is reduced and with it the excessive use of medicines that cost so much result for the Cuban economy [32].…”
Section: Discussionmentioning
confidence: 68%
“…Although before the intervention we found that the variables were unsatisfactory, we now propose that the expected results were obtained, coinciding with other educational interventions already carried out, where up to 79% and 85% of satisfactory results were achieved . When comparing the data obtained with the empirical investigations carried out after the intervention, it can be seen that the results are in tune with the current trends in the effectiveness of the interventions, with the one proposed by this research being one of the most satisfactory and significant results [26][27][28][29][30][31]. The economic valuation and the social contribution are evident in that these results affect not only the individual welfare but social, with the decrease of these infections from an early age, the risk of infection is reduced and with it the excessive use of medicines that cost so much result for the Cuban economy [32].…”
Section: Discussionmentioning
confidence: 68%
“…Nesse aspecto, na medida em que estudantes afirmam sobre a falta de entendimento/conhecimento, motivo pelo qual não se previnem adequadamente (12) , reafirma-se a necessidade da importância sobre a discussão dessa temática. À vista disso, é possível inferir que a evocação do termo "camisinha" possua associação à disseminação do preservativo masculino enquanto método diretamente relacionado às questões contraceptivas.…”
Section: Resultsunclassified
“…Therefore, it is necessary to take a closer look at this manifestation, which requires special attention from health professionals, since the individuals to whom the health care is destined to have a prior reading of the world, based on their life experiences and their socio-cultural contexts. 15 A study 16 discussed the importance of providing a welcoming environment to adolescents through the active search and dialogue between health services and schools, since the school space is a great place for frequent and continuous contact with adolescents, and can be established in an environment conducive to the development of a healthy lifestyle. 17 In this configuration, the other bioecological systems of human development were observed: 5 exo, macro and the chronosystem of adolescents, and in this set, they interact with other elements that reinforce the social and programmatic vulnerabilities of STIs/HIV/AIDS, among them, the poor access to health goods and services and the widespread drug scenarios in their bioecological systems.…”
Section: Discussionmentioning
confidence: 99%
“…Upon reaching the service, the individual may be in a vulnerable situation, but the way in which the individual is received will influence the type of relationship that they will establish with the team. 15 Regarding the acquisition of condoms, a study revealed that some young people do not receive them because they are underage. 19 Although health units provide the condoms for free, the delivery is considered a hostile space for the adolescents .…”
Section: Discussionmentioning
confidence: 99%